2020
DOI: 10.1186/s12884-020-03164-8
|View full text |Cite
|
Sign up to set email alerts
|

Trends in and predictors of pregnancy termination among 15–24 year-old women in Nigeria: a multi-level analysis of demographic and health surveys 2003–2018

Abstract: Background Three-quarters of pregnancy terminations in Africa are carried out in unsafe conditions. Unsafe abortion is the leading cause of maternal mortality among 15–24 year-old women in Sub-Saharan Africa. Greater understanding of the wider determinants of pregnancy termination in 15–24 year-olds could inform the design and development of interventions to mitigate the harm. Previous research has described the trends in and factors associated with termination of pregnancy for women of reproductive age in Nig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
39
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(48 citation statements)
references
References 37 publications
8
39
1
Order By: Relevance
“…Similarly, both the married and the divorced youth mothers had an increased risk of abortion relative to the unmarried ones. The finding is consistent with other studies in Ethiopia, another Africa, and non-African countries [22,23,31]; ( Table 2).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Similarly, both the married and the divorced youth mothers had an increased risk of abortion relative to the unmarried ones. The finding is consistent with other studies in Ethiopia, another Africa, and non-African countries [22,23,31]; ( Table 2).…”
Section: Discussionsupporting
confidence: 93%
“…It is consistent with a study by Van Rensburg that showed societal poverty, unemployment, and other socio-demographic factors affected youth pregnancies and might lead to abortion [28]; (Table 1). Abortion was increased with increased age so that age group 20-24 had more abortion than15-19 The finding is in agreement with that of Nigerian DHS where abortion was 2.34 higher among those aged 20-24 than youths aged 15-19 [23]. It might show that age is the risk of abortion during the younger time because of the lack of information and less self-relying decision making.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Majority of induced abortions, stillbirths and miscarriages occur in low-and middle-income countries (LMICs) and the sub-Saharan African region ( Bearak et al, 2020 ). Studies have also found that the risk of pregnancy termination is high among adolescent girls and young women (AGYW) compared to older women ( Leppälahti, Gissler, Mentula, & Heikinheimo, 2012 ; Onukwugha, Magadi, Sarki, & Smith, 2020 ; Sánchez-Páez & Ortega, 2019 ). One of the major risk factors for pregnancy termination is intimate partner violence (IPV) ( Durevall & Lindskog, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, in SSA, only country-specific studies have been carried out in Cameroon ( Alio et al, 2011 ), Ethiopia ( Tiruye, Chojenta, Harris, Holliday, & Loxton, 2020 ), Ghana ( Tenkorang, 2019 ), Nigeria ( Bola, 2016 ) and Tanzania ( Stöckl, Filippi, Watts, & Mbwambo, 2012 ) on the association between IPV and pregnancy termination. None of these studies specifically focused on AGYW, despite previous studies recording high prevalence of pregnancy termination among this cohort of women ( Leppälahti et al, 2012 ; Onukwugha et al, 2020 ; Sánchez-Páez & Ortega, 2019 ). The current study seeks to fill this gap by examining the association between IPV and pregnancy termination among AGYW in 25 sub-Saharan African countries using recent Demographic and Health Surveys (DHS) data from 2010 to 2019.…”
Section: Introductionmentioning
confidence: 99%